1990
DOI: 10.1111/j.1365-2230.1990.tb02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Introital adenosis associated with the Stevens-Johnson syndrome

Abstract: A young woman presented with erosive lesions of the labia minora, which appeared 3 years ago after Stevens-Johnson syndrome. Pathological examination showed 'vulval adenosis'. A similar case has been previously reported. Vaporization by carbon-dioxide laser gave satisfactory results, and after 2 years the patient remains totally cured. We discuss several embryological theories which may explain the mechanism of the vulval adenosis in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 2 publications
1
16
0
1
Order By: Relevance
“…[11][12][13] Vulvar adenosis, the abnormal presence of mucinous and/or tuboendometrial epithelium in the labia minora, has been reported to follow both SJS and TEN. [14][15][16][17] This condition tends to occur in young women, and it can present several years after the episode of disease. The clinical presentation is that of tender, erosive, hemorrhagic lesions.…”
Section: Clinical Aspects Of Sjs/tenmentioning
confidence: 99%
“…[11][12][13] Vulvar adenosis, the abnormal presence of mucinous and/or tuboendometrial epithelium in the labia minora, has been reported to follow both SJS and TEN. [14][15][16][17] This condition tends to occur in young women, and it can present several years after the episode of disease. The clinical presentation is that of tender, erosive, hemorrhagic lesions.…”
Section: Clinical Aspects Of Sjs/tenmentioning
confidence: 99%
“…Treatment is mainly supportive as for toxic epidermal necrolysis as the role of steroids and other disease-modifying treatments is not established. Bonafe et al (1990) found treatment with the laser helpful in dealing with adhesions; surgical procedures may also be employed (Chapter 10).…”
Section: Stevens-johnson Syndromementioning
confidence: 99%
“…It may also occur after trauma, for example treatment with 5-fluorouracil (Goodman et al 1991), or following laser therapy (Sedlacek et al 1990). Vulval and lower vaginal adenosis is rarer and appears usually to arise following severe erosive inflammatory disease such as Stevens-Johnson syndrome (Bonafe et al 1990), toxic epidermal necrolysis (Adornato 2000), lichen planus (Singer et al 1994), pemphigus and as a complication of laser therapy.…”
Section: Vulvovaginal Adenosismentioning
confidence: 99%
“…The same study also demonstrated that such cases can often be successfully corrected surgically [88]. Limited histopathologic studies have demonstrated edema and inflammation, epithelial metaplasia of the introital epithelium, and hyperplastic glandular structures in the mucosa [78,79]. It was later theorized that vaginal ulcerations may lead to squamous metaplasia as a component of the pathogenesis of vaginal complications of SJS/TEN [89].…”
Section: Gynecologic/genitourinarymentioning
confidence: 95%
“…Many other smaller reports have also described vulvar pain and dyspareunia following SJS/TEN. Examination of these patients revealed vulvar and vaginal adenosis, vaginal stenosis, fusion of the labia minora and majora, and cases of complete vaginal fusion leading to hematocolpos and hydrocolpos [76,[78][79][80][81][82][83][84][85][86]. All of these findings place significant limits on meaningful menstruation and may result in subfertility or frank infertility [86,87].…”
Section: Gynecologic/genitourinarymentioning
confidence: 98%